Developing support strategies to enhance tuberculosis treatment adherence in Sekhukhune District Clinics, Limpopo Province - Maseko, Raesibe Gloria (My University, 2024)
Background: South Africa (SA) is among the countries that are challenged by Tuberculosis (TB). Active TB patients require daily administration of medicines for six months or longer with no interruption. This can be achieved through great adherence as well as a proper support system. The study aimed to develop support strategies to enhance TB treatment adherence in the Sekhukhune District clinics, in the Limpopo Province. Method: The study used a quantitative research method. The method was considered to be relevant to this study as the research aimed to develop support strategies to enhance TB treatment adherence at selected clinics in the Sekhukhune District. Data was collected from five selected clinics in the Sekhukhune District, using questionnaires and analysed using the Statistical Package for the Social Sciences (SPSS) version 29. A total of 90 respondents from a population of 116 participated in the study. Simple random probability sampling was used. The questionnaires were piloted in a different setting to ensure reliability. The outcomes of the analysis were presented as frequencies and percentages in tables, bar graphs and pie charts. Ethical standards were considered throughout the study. Results: The study revealed that several factors contribute to TB treatment adherence. These factors include but are not limited to demographic, patient-related, socio-economic, healthcare system, disease and medication-related, as well as adherence and supportrelated factors. The results of the study revealed that there is a lack of support from family as well as the community and there is also a lack of knowledge about TB and its treatment. Support strategies were developed to enhance TB treatment adherence in selected clinics in the Sekhukhune District of the Limpopo province. Conclusion: The study concluded that several factors hinder the adherence to TB treatment at the Sekhukhune District clinics in the Limpopo Province. Inadequate support and information about TB treatment, the treatment side effects, the comorbidities and the lack of Directly Observed Therapy (DOT) supporters are the main findings of this study.
Thesis (M. (Nursing Science)) -- University of Limpopo, 2024
Keywords: Adherence; contacts; Defaulter; Enhance; Patient; Strategies; Treatment; Tuberculosis; Tuberculosis; Antitubercular agents; Tuberculosis -- Alternative treatment; Patient compliance